Efek Amelioran pada Pertumbuhan dan Produksi Tanaman Jagung Manis - Elfarisna Elfarisna; Erlina Rahmayuni; Helfi Gustia (Institut Pertanian Bogor, 2023)
Ameliorant is a substance that can increase soil fertility by improving the soil's physical, chemical, and biological conditions, and it can be organic or inorganic. Some ameliorants often used are manure, lime, or a combination of all these fertilizers. This study aimed to determine the effect of ameliorants on the growth and production of sweet corn. The study was conducted at the Experimental Station of the Faculty of Agriculture, University of Muhammadiyah Jakarta, from July to October 2022. The study used a Randomized Completely Block Design with five ameliorant treatments and five replications, so there were 25 experimental units. Each experimental unit consisted of three plants. The treatments given were P0 (without ameliorant as control)), P1 (calcite 5 g/plant), P2 (dolomite 5 g/plant), P3 (green mussel shell waste 5 g/plant, and P4 (zeolite 5 g/plant). The results showed that ameliorants gave similar results as controls and did not increase the growth and production of sweet corn plants. Keywords: ameliorant, green mussel shell, soil pH